Leading By Heart: A Transformational Leadership Paradigm within the Church Context - Ismail Banne Ringgi' (IAKN TORAJA, 2026)
Leadership within the church context is not solely anchored in formal authority, but rather in the capacity to inspire, serve, and transform congregants. Transformational leadership paradigm, rooted in the principle of “leading by heart,” offers a spiritual approach to nurturing faith communities. It emphasizes accountability, emotional stability, the development of others, vigilance against temptations like wealth, affection, and power, and reverence for God as foundations for authentic relationships. Employing a descriptive qualitative methodology through library research, this study analyses ecclesiastical leadership practices. The findings indicate that heart-centred leadership fosters an inclusive, compassionate communal climate. The implications extend to all ministers in the Gereja Toraja, calling them to shepherd the faithful as agents of transformation. By leading by heart, the church becomes a vibrant space where Christ’s love is tangibly manifested through transformative actions, relationships, and service.